Cancer incidence trends in the Czech Republic - Pehalova, Lucie; Krejci, Denisa; Snajdrova, Lenka; Dusek, Ladislav (Cancer epidemiology, 2021)
BACKGROUND: Evaluation of time trends is an integral part of a comprehensive analysis of cancer data. Our study aimed to assess trends in cancer incidence in the period 1977-2018 in the Czech Republic. METHODS: Cancer data were obtained from the Czech National Cancer Registry. Incidence trends were evaluated using the joinpoint regression. The overall trend for the entire analysed period and the current trend for the last 10 years were determined using the average annual percentage change. RESULTS: In the period 1977-2018, the age-standardised incidence (European standard) of malignant neoplasms excluding non-melanoma skin cancers increased from 518.2 to 681.9 cases per 100,000 population in men, and from 320.9 to 467.2 in women. The largest increase in trend in the analysed period was observed for melanoma, which showed an average annual increase of 4.0 % in men and 3.3 % in women. Over the last decade, a significant increase has been observed for head and neck cancer and oesophageal cancer, mainly in women. On the contrary, the largest decrease in trend in the analysed period was observed for stomach cancer, with an average decrease of 2.9 % in men and 2.8 % in women. Over the last 10 years, a highly significant decrease has also been observed for colorectal cancer: 3.2 % in men and 2.8 % in women. The largest difference in trend between the sexes was recorded in lung cancer: a steady decline of 1.3 % per year was observed for men, but an increase of 3.1 % per year was demonstrated for women. After the introduction of colorectal and cervical cancer screening programmes, a significant decrease of incidence rates for these diagnoses was observed. CONCLUSIONS: Knowledge of the current cancer burden in the population and its time trends will help to prioritise targets and future resource allocation to cancer control.
Keywords: Cancer; Registries; Humans; registrace; Female; nádory děložního čípku; Early Detection of Cancer; lidé; Epidemiology; Time trend; časná detekce nádoru; ženské pohlaví; Male; incidence; Incidence; Czech Republic; Uterine Cervical Neoplasms; Česká republika; mužské pohlaví